2019
DOI: 10.1002/slct.201803796
|View full text |Cite
|
Sign up to set email alerts
|

From Chemical Gardens to Quasibiological Inorganic Cells

Abstract: The formation of closed chemical gardens that resemble quasibiological cells at the macroscale (> 1 cm) is demonstrated. The cells are produced by injecting lanthanide salts in alkaline solutions and do not require silicates. The cells can encapsulate chemicals and enzymes and carry out reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Very recently, we showed that injection of lanthanide solutions in concentrated NaOH solution results in the formation of inorganic cells that grow to centimeter sizes. These cells can act as microreactors for chemical and enzymatic assays . They resemble the visible to the naked eye Thiomargarita namibiensis bacteria, which act as inorganic chemical factory, and the hybrid inorganic cells (iCHELLS), which form upon injection of a solution containing polyoxometalate clusters (like phosphotungstic acid) in a solution containing an organic cation .…”
Section: Figurementioning
confidence: 99%
See 3 more Smart Citations
“…Very recently, we showed that injection of lanthanide solutions in concentrated NaOH solution results in the formation of inorganic cells that grow to centimeter sizes. These cells can act as microreactors for chemical and enzymatic assays . They resemble the visible to the naked eye Thiomargarita namibiensis bacteria, which act as inorganic chemical factory, and the hybrid inorganic cells (iCHELLS), which form upon injection of a solution containing polyoxometalate clusters (like phosphotungstic acid) in a solution containing an organic cation .…”
Section: Figurementioning
confidence: 99%
“…[10] In the search forn ew applicationsi nc hemobrionics, it was realized that these inorganicc ellsc ould be used as drug or biomolecular deliverys ystemss inceb ecause are closed structures that can compartmentalizev ariouscompounds.However, the previouslyg enerated terbium hydroxides were sensitive to mechanical stress and easy to break. [7] Therefore, here we first investigated whether inorganic cellsc omposed of calcium silicate membrane, which is ab iological inert material, can be generated and whethert hey can be loaded with biomolecules for sustained release.For this, 100 mlo f0 .5 m CaCl 2 solution were injected in a 3.50 %s odium silicate (expressed as SiO 2 )s olution. Figure1 showst he formation of calcium silicate cells.T he use of higher (1.0 m)o rl ower (0.25 m)c oncentrations of CaCl 2 resulted in the development of either tubular structures (regularc hemical gardens)o rs piral structures that grow on the surfaceo ft he solution ( Figure 1A).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…These studies focused on various physicochemical factors [6][7][8][9][10][11][12][13][14][15] including oscillatory growth of hollow microtubes, 12 tube growth with a pinned bubble, 14 and spiral growth of the tube controlled by the application of magnetic force. 15 Recently, chemical gardens have received attention as biomimetic materials due to their ability to form a variety of self-assembled structures, [16][17][18][19][20][21][22][23][24][25][26][27] such as silica-rich biomimetic mineral 20 and selfassembled nanostructures. [21][22][23][24][25][26][27] These diverse approaches to chemical gardens and their self-organizing processes in physics, chemistry, and biology nucleated a new research area called ''chemobrionics''.…”
Section: Introductionmentioning
confidence: 99%